Design methods for low volume roads - Brito, Lelio (2011)
This thesis is concerned with producing a simple method to design low volume roads (LVR) by means of a rationale which accounts for permanent deformation development in granular layers. Rutting is regarded as the main distress mode in unsealed and thinly sealed pavements. Hence, it is desirable that it be analytically approached rather than empirically, as in most design methods. The overall aim of this PhD thesis was to look into the behaviour of in-service roads and from a newly developed process, to advance, in a systematic manner, the elements required to produce a simple mechanistic design procedure. The study took as its basis an assessment of the proximity of the stress distribution in the pavement to the material’s failure envelope.